Indonesian Banking Efficiency: Transmission to the Financial Stability Confronting ASEAN Economic Community - Ajija, Shochrul Rohmatul; Yasin, Mohammad Zeqi; Albra, Reno (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
Banks are a particular type of institution within the financial system that have influence on financial stability. Their readiness will determine the governmentâs policy, notably in an economic era of integration. In the case of South East Asia, there is the ASEAN Economic Community (AEC) which facilitates economic integration to strengthen allthe member countries. This study aims to measure bank efficiency (conventional and shariah) in Indonesia, and also establish the transmission scheme based on the estimated result through financial stability issues confronting the AEC. Data Envelopment Analysis (DEA) is used to estimate banking efficiency statically and dynamically (Malmquist Index). The result showed that technical efficiency of conventional banks is statically better than shariah banks. Meanwhile, dynamically, considering technological index, both types of banks have good results. The optimizing effort by each bank in order to increase their input utilization can be maintained through intensification of the financial program and making it more comprehensive. Subsequently, this effort hopefully can increase the number of financial participants. Eventually, increasing the number of participants will strengthen the financial stability of Indonesia.